Room‐Temperature In‐Situ Design and Use of Graphene Oxide‐SBA‐16 Composite for Water Remediation and Reusable Heterogeneous Catalysis. Issue 5 (17th February 2017) - Chaudhuri, Haribandhu; Dash, Subhajit; Gupta, Radha; Pathak, Devendra Deo; Sarkar, Ashis
Abstract: In this paper, we report an in‐situ facile route to synthesize graphene oxide‐SBA‐16 (GO‐SBA‐16) composite in acidic medium at room temperature. Thermogravimetric analysis (TGA) exhibits excellent stability of the synthesised composite. X‐ray diffractograms (XRD), Fourier transformed infrared (FTIR) spectroscopy, and nitrogen sorption isotherms indicated the coexistence of GO and mesoporous silica particles in the composite. Moreover, field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) images gave clear evidence of the formation of GO‐SBA‐16 hybrid composite. Apart from this, the synthesised hybrid material shows not only highly proficient sorption capacities of toxic dyes but also excellent catalytic performance. The highly proficient sorption capacity of GO‐SBA‐16 towards toxic dyes (qm : 358.72 mg g −1 for Malachite Green, MG; qm : 536.63 mg g −1 for Methyl Violet, MV) can be explained on the basis of both hydrogen bonding and electrostatic interactions between the surface of GO‐SBA‐16 and dye molecules. Furthermore, GO‐SBA‐16 shows excellent catalytic efficiency towards metal free synthesis of amide from secondary amine and aromatic aldehyde. Finally, used GO‐SBA‐16 can be well regenerated and reused several times without causing any important decrement in the sorption efficacy and catalytic activity. Abstract : In‐situ room‐temperature fabrication of Graphene oxide‐SBA‐16 composite and its potential applications in water treatment and catalysis